Efficiency of public spending on human capital in Africa - Isaiah Sikayena; Isaac Bentum-Ennin; Francis Kwaw Andoh; Richard Kofi Asravor (Cogent Economics & Finance, 2022)
Government spending on human capital continues to increase over the years. However, knowledge of the efficiency of such spending is limited. Using data from World Bank's World Development Indicator and World Governance Indicator from 2006 to 2017 and Data Envelopment Analysis and DEA Bootstrapping models, the study examined the relative technical efficiencies of public spending on human capital and their correlates in Africa. The study found public spending on health and education in Africa to be inefficient. Efficiency was much higher in health spending than in educational spending. Factors such as institutional quality, economic growth, government expenditure, foreign direct investment, and trade openness were found to influence the efficiency of public spending on human capital. Government should put in place measures to stimulate trade, ensure institutional quality and growth of urbanization to help improve efficiency in public spending.
Keywords: H5; H51; H52; 330; education; efficiency; health; human capital; public spending on education; public spending on health